If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(a + -2) + 3 = 3a + -15 Reorder the terms: 6(-2 + a) + 3 = 3a + -15 (-2 * 6 + a * 6) + 3 = 3a + -15 (-12 + 6a) + 3 = 3a + -15 Reorder the terms: -12 + 3 + 6a = 3a + -15 Combine like terms: -12 + 3 = -9 -9 + 6a = 3a + -15 Reorder the terms: -9 + 6a = -15 + 3a Solving -9 + 6a = -15 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -9 + 6a + -3a = -15 + 3a + -3a Combine like terms: 6a + -3a = 3a -9 + 3a = -15 + 3a + -3a Combine like terms: 3a + -3a = 0 -9 + 3a = -15 + 0 -9 + 3a = -15 Add '9' to each side of the equation. -9 + 9 + 3a = -15 + 9 Combine like terms: -9 + 9 = 0 0 + 3a = -15 + 9 3a = -15 + 9 Combine like terms: -15 + 9 = -6 3a = -6 Divide each side by '3'. a = -2 Simplifying a = -2
| 2x+12=-16-2x | | 3(x+1)-5=-3x+2 | | 4x-26=2x+22 | | 8x+12=6x-28 | | 6.2n+5-1.4n=4.8h+5 | | -6(-3-8)=15+7n | | 32-(9x)=140 | | X^2-12x+y^2-18y=-108 | | -5x-10=9x+18 | | 62=2l+2(19) | | -8-2r=-4r-4 | | 27y^3-64x^3=0 | | 25x+11=x+83 | | 26-2x=7(x-4) | | X^2-12x+y^2-18y+108=0 | | 1=6b | | -6(3x+4)=156 | | 3x+3x+x-5+x-5=x+10+x+x | | -5d=10-3d | | (6x+y)dx+(4x+y)dy=0 | | 10x+10y=4x+7y | | 2.5(t-22)-6=9 | | 8-3x=-8+5x | | vp=3nv+-4p | | 4x-5=3x+25 | | 9x-4=7x+12 | | 40k+80=30k+10 | | 8-3x=8+5x | | -112=-9k+5 | | 8+6y=10y | | -3y+6x=4 | | 9q=6q+3 |